All quiet on the western front? The evolutionary history of monogeneans (Dactylogyridae: Cichlidogyrus, Onchobdella) infecting a West and Central African tribe of cichlid fishes (Chromidotilapiini) - Moons Tanisha; Kmentová Nikol; Pariselle Antoine; Artois Tom; Bert Wim; Vanhove Maarten P.M.; Cruz-Laufer Armando J. (Parasite, 2023)
Owing to the largely unexplored diversity of metazoan parasites, their speciation mechanisms and the circumstances under which such speciation occurs – in allopatry or sympatry – remain vastly understudied. Cichlids and their monogenean flatworm parasites have previously served as a study system for macroevolutionary processes, e.g., for the role of East African host radiations on parasite communities. Here, we investigate the diversity and evolution of the poorly explored monogeneans infecting a West and Central African lineage of cichlid fishes: Chromidotilapiini, which is the most species-rich tribe of cichlids in this region. We screened gills of 149 host specimens (27 species) from natural history collections and measured systematically informative characters of the sclerotised attachment and reproductive organs of the parasites. Ten monogenean species (Dactylogyridae: Cichlidogyrus and Onchobdella) were found, eight of which are newly described and one redescribed herein. The phylogenetic positions of chromidotilapiines-infecting species of Cichlidogyrus were inferred through a parsimony analysis of the morphological characters. Furthermore, we employed machine learning algorithms to detect morphological features associated with the main lineages of Cichlidogyrus. Although the results of these experimental algorithms remain inconclusive, the parsimony analysis indicates that West and Central African lineages of Cichlidogyrus and Onchobdella are monophyletic, unlike the paraphyletic host lineages. Several instances of host sharing suggest occurrences of intra-host speciation (sympatry) and host switching (allopatry). Some morphological variation was recorded that may also indicate the presence of species complexes. We conclude that collection material can provide important insights on parasite evolution despite the lack of well-preserved DNA material.